Mitochondria-targeted strategies in tumor immunity - Cheng, Xudong; Wang, Yian; Johnson, Bryon; You, Ming (Frontiers in Immunology, 2025)
Mitochondria, as regulators of cellular energy production and metabolism, play a crucial role in tumor growth and survival. Tumors are reprogrammed to accommodate rapid proliferation through the Warburg effect. This reprogramming leads to the accumulation of metabolites such as lactate and ketone bodies, thereby lowering the pH of the tumor microenvironment, inhibiting the activity of effector T cells and NK cells, while promoting the infiltration of regulatory T cells and MDSCs, forming an immunosuppressive microenvironment. ROS produced by mitochondria can affect immune cell function by modulating their signaling pathways. Mitochondria also release DAMPs, which activate the antigen-presenting capacity of dendritic cells and initiate anti-tumor immune responses. Currently, various methods have been employed, such as DLCs modifications and mitochondrial targeted delivery, which enable drugs to penetrate the lipid bilayer and enter the mitochondria, thereby helping to reduce immunosuppression in the tumor microenvironment. In this review, we will discuss the impact of mitochondria on tumor immunity, strategies to target tumor cell mitochondria, and progress on the discovery of mitochondria-targeted drugs to enhance tumor immunity, providing potential directions for developing new cancer therapeutic strategies.